Materials, technology and special equipment for strengthening and restoration of dies for pressing the hollow cylindrical refractory. Part 1. Analysis of wear conditions and dies metal durability studies, weld standard electrode materials. - Андрущенко, М.И.; Осипов, М.Ю.; Куликовский Р.А., Р.А.; Капустян, А.Е.; Магда, Е.С. (Problems of Tribology, 2016)
The analysis of the structure of the scheme, dies wear conditions for pressing the hollow cylindrical refractory products and defined requirements to them. It is shown that in addition to relatively high wear resistance of working edges of dies, they must resist the working surface caricaturing refractory mass and level of ductility and toughness of the metal shear-ing edges should exclude fragments thereof during operation.Conventionally, commercially available materials (stick electrodes and flux cored wires) selected for laboratory tests on the chemical composition and structure of the weld metal, are divided into seven groups (first and second group rep-resented by one electrode material, the other two - five):1 – low-carbon materials doped with ferrite or ferrite-pearlite structure;2 – low-carbon high-alloy with a structure of stable and unstable austenite;3 – high-carbon, high-alloy with a stable austenite structure;4 – medium-carbon, medium-doped structure consisting of low-carbon martensite and bainite;5 – with a predominantly martensitic metal structure, in some cases, a small amount of carbides;6 – Metal hypoeutectic composition with a predominantly austenitic matrix or austenito-martensitic matrix, holding 10 - 25 % of carbides (CrFe)7C3;7 – metal hypereutectic composition comprising a large amount of carbides or сarboborides (50 - 60 %), are in the martensitic-austenitic matrix with austenite content from 0 to 55 %.According to the latest classification of surfacing materials of the International Institute of welding the materials in question are ten of the sixteen structural groups, provided this classification - M1, M2, M3, M4, MK1, A1, A2, A3, ACP and AEC.Laboratory tests for abrasion resistance have shown that the wear resistance within the investigated range of mate-rials during the transition from the first to the seventh group is increased 25-fold. However, it does not depend on the initial hardness, but is correlated with the friction surface microhardness acquired during wear. The greatest increase in microhard-ness (4.1 GPa), is observed on the working surface of the layer of deposited metal type 65H11N3, due to the formation of 15-20 % martensite deformation. At comparable levels microhardness higher wear resistance materials are characterized, the structure of which, along with deformation martensite, there is a relatively plastic austenitic component.